A New Formula for Optimized Weight Estimation in Extreme Fetal Macrosomia (≥ 4500 g) - Faschingbauer, F.; Beckmann, M. W.; Goecke, T. W.; Yazdi, B.; Siemer, J.; Schmid, M.; Mayr, A.; Schild, R. L. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: To develop and to evaluate a specific sonographic weight formula for fetuses with extreme macrosomia (≥ 4500 g). Materials and Methods: A statistical estimation technique known as “gradient boosting with component-wise P-splines” was applied to a group of 174 fetuses with a birth weight (BW) ≥ 4500 g. Each fetus underwent an ultrasound examination with complete biometric parameters within 7 days of delivery. The exclusion criteria were multiple pregnancy, intrauterine death, and major structural or chromosomal anomalies. A new formula was derived using the obtained data and was then compared to currently available equations for estimating weight in the macrosomic fetus. Results: The new formula is: log10 (EFW) = 3.6687781710 – 0.0003 230 278 × (BPD – 100.4080) – 0.0000843433 × (BPD – 100.4080)^2 + 0.0007281 281 × (OFD – 120.6322) + 0.0000664323 × (OFD – 120.6322)^2 + 0.000000001794019 × exp(ATD – 120.1552) + 0.0005946974 × (APAD – 121.2069) – 0.0000210137 × (APAD – 121.2069)^2 – 0.000003318 × (APAD – 121.2069)^3, where EFW is the estimated fetal weight, BPD is the biparietal diameter, OFD is the occipitofrontal diameter, ATD is the abdominal transverse diameter, and APAD is the abdominal anteroposterior diameter. The new formula proved to be superior to other established equations, showing the lowest mean absolute percentage error (MAE 2.506), the smallest variance regarding the signed percentage error (SPE) (SD 3.376), and the best distribution of absolute percentage errors within prespecified error bounds. Conclusion: This new formula significantly improves weight estimation in fetuses with extreme macrosomia.
Keywords: ultrasound 2 D; obstetrics; observer performance; fetus